Planejamento orçamentário para uma empresa do segmento varejista de máquinas agrícolas - Trindade, Matheus (2022)
Agribusiness has a strong direction of economic investments in the country, but it is governed by macroenvironment factors that can result in financial instability in the sector. Therefore, designing a budget is essential to mitigate the negative effects of this instability, combining strategic planning with business administration. This work projected the budget of an agricultural concessionaire for the year 2023 based on the analysis of historical data during 12 months of its income statements, through quantitative exploratory-experimental research of all the company’s accounting accounts, emphasizing the most influential groups. The annual projection indicated an increase of 2.48 to 3.98% in net income, mainly explained by an improvement in operating performance, corroborating the estimates and guidelines expected by the company. The construction of the theoretical model of the budget tends to help in making decisions regarding short-term financial investments by the company and to predict suggestions for taking advantage of opportunities and/or containment of damages, in order to guarantee a sustainable cash flow and the maintenance of your working capital.